Code-based authentication with designated verifier. (2016) - Ren, Yan; Wang, Hongbin; Du, Jiali; Ma, Liqiong
The public key encryption scheme based on the bounded decoding problem was first introduced by McEliece in 1978. Since then, several code-based signature schemes have been designed. Most of them have been analysed and proven secure against different types of adversaries. However, researchers have given less attention to the code-based strong Designated Verifier Signature (DVS) scheme. In this paper, we introduce a new strong DVS scheme. It is based on CFS signature and Stern's identification scheme, whose security depends on syndrome decoding problem and bounded decoding problem. The proposed scheme is the first code-based strong DVS, and also satisfies the strong designated verifier, unforgeability and non-delegatability properties which are the security requirements for a strong DVS.